Collective Bargaining in the Public Sector : A Re-Examination - Williams, C. (Relations industrielles / Industrial Relations, 1973)
This paper calls for a new direction in the study of public sector collective bargaining away from the «issue» and «problem» approach in favor of a re-examination, in the light of our experience over the past decade, of the physiology of the technique itself with particular reference to the appropriateness of current public sector collective bargaining structures.